Caracterización Geológica Geotécnica de la vía Zaruma – Roma, Tramo Pillacela-Roma, Cantón Zaruma, Provincia de el Oro. - Narváez Pineda, Jimmy Leodan (2024)
The present reserch called “Geotechnical Geological Characterization of the Zaruma – Roma road, Pillacela-Roma Section, Zaruma Canton, Province of El Oro” has the purpose of knowing the geotechnical behavior of the soil, for which were determined the physical mechanical properties of geo-materials of the road under study, which includes an extension of 2,097 km and an area of 83 hectares. The reserch began with the topographic survey at a scale of 1:5000, which served as a basis for the geological survey, allowing the determination of the existing lithology in the study route; Subsequently, the geomorphology and slopes were analyzed to know the most critical areas where the focus will be made in greater detail. Through in situ field visits, the most relevant slope movements in the study area were determined, in which direct and indirect tests were carried out. Within the direct tests, a total of 4 standard penetration tests (SPT) were applied. From the samples obtained, the respective procedure was carried out in the DICONS soil laboratory, obtaining the granulometry, moisture content, Atterberg limits and classifications. AASTHO and SUCS using ASTM standards and 3 direct cuts, which were used to obtain the angle of friction and cohesion. For the indirect tests, 3 vertical probing tests were applied, allowing us to know the arrangement of the soil layers. With the information collected, the global stability of the slopes was analyzed in the Slide 6.0 program in the current state and with seismic load. The results obtained show that slopes 1 and 3 are unstable, while slope 2 is in a Critical state. Keywords, geology, geotechnics, SPT, SEV, safety factor, stability.